Optimal Participation in Manual Frequency Restoration Reserve-Based Demand Response Programs for Large Consumers - Jose Arellano; Alvaro Garcia-Cerezo; Miguel Carrion (IEEE Access)
The increasing penetration of intermittent, weather-dependent generation has heightened the need for flexibility in power systems. Traditionally passive, consumers are now being encouraged to actively support ancillary services to help balance generation and consumption. This work examines the participation of a large electricity consumer in manual frequency restoration reserve-based demand response programs. In particular, the Active Demand Response Service (ADRS), recently introduced in Spain, is addressed. Participation involves submitting power-price bids in an annual auction, indicating the amount of grid consumption the consumer is willing to reduce upon request by the system operator. The problem is modeled as a three-stage stochastic optimization, considering three key decisions: the power bid submitted to the auction, the operational decisions of the consumer before ADRS participation, and operational adjustments when ADRS is activated. A cement producer serves as the case study, with several scenarios comparing different electricity procurement options: grid-only supply, photovoltaic self-generation, and battery storage. The results show that consumers with alternative energy sources, such as solar or batteries, are less inclined to participate in ADRS due to the requirement to maintain a minimum level of grid consumption. Nevertheless, participation in ADRS can offer substantial economic benefits, especially at auction prices observed in previous editions. In this regard, the cement producer considered in this case study could achieve an expected cost savings of up to 30% annually by participating in this service. Moreover, the fixed remuneration from the ADRS could significantly offset the plant’s operational costs, covering between 28% and 42% when participating with approximately 5 MW in ADRS.